Information and communication technologies: interfaces the nursing work process - Luana dos Santos Costa; Ítalo Rodolfo Silva; Thiago Privado da Silva; Marcelle Miranda da Silva; Isabel Amélia Costa Mendes; Carla Arena Aparecida Ventura (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to unveil the meanings that nurses attribute Information and Communication Technologies for the nursing work process Methods: qualitative research, theoretically and methodologically based on the Complexity Theory and on the Grounded Theory, respectively. Research with 19 participants, being 12 clinical nurses, and 7 resident nurses. Semi-structured interviews were used for data collection. Results: the results revealed the meanings that clinical nurses attribute to Information and Communication Technologies and, thus, the motivations and limitations for the use of these technologies, pointing out possibilities and strategies that impact the nursing work process, based on the interactions promoted by the official and non-official use of these resources. Final Considerations: the meanings that nurses attribute to Information and Communication Technologies are dependent on their ability to successfully employ those technologies and their importance to the work process developed by the professionals.